Relation of Service Quality, Load Factors and Tariff on Bus City of Bandung - Novirani, Dwi; Adianto, Hari (International Review of Management and Marketing, 2020)
The purpose of this study is to discuss the relationship between satisfaction with service quality, by determining the number of vehicles and the ideal tariff for passengers. This research was conducted on consumers who use the Bandung City Bus. The relationship between satisfaction and service quality with passenger loyalty using the Structural Equation Modeling (SEM) method, the ideal tariff is seen from the Ability and Willingness To Pay passengers compared to vehicle operating costs, the break-even load factor method is used to calculate the number of vehicles that consider passenger needs, revenue, and operational costs. The results of the calculation of service quality on satisfaction is 6,731, proving that service quality has a significant and positive influence on customer satisfaction. One of the dimensions of service quality is tangible include physical evidence has the higest correlation with satisfaction factors on the service quality dimension affecting passenger loyalty. Service satisfaction is obtained from vehicles are load factors, and tariffs, which are calculated from six non-toll routes in Bandung, with the Ability to Pay vehicle suitable tariffs, only route 6B shows the Willingness to Pay customers below the current tariff. Keywords: Service Quality; Customer Satisfaction; Load Factors, Tariff JEL Classifications: L1, L8 DOI: https://doi.org/10.32479/irmm.9867